Clinical, Epidemiological and Demographic Profile of Patients Undergoing Holter (24 h) at a Health Center in Belém do Pará: a Retrospective Study - Pereira, Fábio Benedito Filo Creão Garcia; Trivilin, Lizandra Lujan Delpupo; Torres, Marcia Rayssa Farias (JOURNAL OF CARDIAC ARRHYTHMIAS, 2021)
Introduction: Dynamic electrocardiography by the Holter system can be divided into four major groups: evaluation of clinical manifestations related to the presence of altered heart rhythm; assessment of myocardial ischemia; risk assessment of future cardiac events; and therapeutic assessment. Objective: To identify the clinical, epidemiological and demographic profile that is associated with electrocardiographic changes in the 24-hour Holter in patients seen at the Escola do Marco Health Center in Belém do Pará, Brazil. Methods: We carried out a cross-sectional and retrospective study, with data from patients such as: clinical and electrocardiographic correlation, indications, tachyarrhythmias, bradyarrhythmias, medications in use, provenance, demographic data and behavior modification. All of the information was compiled in a standardized protocol. Results: The main electrocardiographic findings were: supraventricular and ventricular extrasystoles less than 1% (reported in 71 and 57% of patients, respectively). Conclusion: The 24-hour Holter still has an important role in the identification of patients with electrocardiographic changes. The main indications for the examination were to assess the severity of arrhythmia (32%) and palpitation to clarify (23%), and there were uncommon findings, but of great clinical importance and with statistical significance, such as almost three times more frequent nonsustained ventricular tachycardia in patients with heart failure, cardiac, symptomatic frequent extrasystole (> 3%), more frequent atrial fibrillation in the elderly and men (60%) and with underuse of anticoagulant therapy (20%) due to non-diagnosis prior to the exam, and changes in the ST segment with a tendency in patients with systemic arterial.